Hypoplastic aorto-iliac syndrome and hypoplasia of the vena cava and iliac veins presenting as simultaneous left leg claudication and iliofemoral deep venous thrombosis - Devon Kelley; Randy Shafritz (SAGE Open Medical Case Reports)
Hypoplastic aorto-iliac syndrome is an unusual cause of claudication or limb ischemia. Hypoplasia of the vena cava and iliac veins is an even rarer entity and is usually found incidentally in patients presenting with extensive deep venous thrombosis or unexplained pulmonary embolism. Both are thought to be due to in-utero developmental defects or vascular accidents during maturation of the fetus. Each entity is so rare that only short series or case reports are found in the literature. We report an unusual case of a 64-year-old Caucasian male with no atherosclerotic risk factors who presented with a 2-month history of left hip and leg pain, followed by significant left leg swelling. Venous duplex confirmed the diagnosis of deep venous thrombosis and anticoagulation therapy and compression were initiated. Because of worsening symptoms, percutaneous venous thrombectomy was attempted with only a small amount of thrombus extracted. Venography and intravascular ultrasound revealed a hypoplastic, chronically occluded inferior vena cava and iliac veins without thrombus, venous collaterals, or an enlarged azygous system. CT angiography confirmed hypoplasia of the venous system but also revealed a severely diseased aortoiliac system with a chronically occluded left common iliac artery and reconstitution of the left common femoral artery via a large lumbar collateral vessel. Despite improvement in venous symptoms, disabling left leg claudication persisted. Aortoiliac stenting was performed but failed within 6 weeks. The patient then underwent a successful aortobi-iliac bypass with a Dacron graft for his arterial insufficiency. The aorta was noted to be thickened, fibrotic, and mildly atherosclerotic, with thrombus throughout the aorta and iliac arteries. Hypoplastic aortoiliac syndrome and hypoplasia of the vena cava and iliac veins are both rare entities. To our knowledge, this is the first published case report describing both entities in a single patient. In addition, this may be the first published report of both conditions requiring simultaneous invasive treatment.